Q. 365.0( 3 Votes )

The 4<su

Answer :


Let a and r be the first term and common ratio respectively.
Then a = -3

4th term = a4 = ar3 = -3r3

2th term = a2 = ar = -3r
a4 = (a2)2

-3r3 = (-3r)2

-3r3 = 9r2

r = -3

7th term = a7 = ar6 = -3(-3)6 = -3(-3)6= (-3)7 = - 2187

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses